Mercy as a Public Virtue - Flores, Nichole (Journal of religious ethics, 2020)
James F. Keenan defines mercy as “the willingness to enter the chaos of another.” Mercy thus defined, he argues, is the distinctive characteristic of Christian morality. This essay asserts that mercy is, in fact, a public virtue, one that can be affirmed across a broad range of religious and moral traditions. As a public virtue, mercy ought to shape both affective and effective responses to the Syrian refugee crisis in the United States.